Organogenesis of Cavendish Banana (Musa acuminata L.) Plant in Various Concentrations of ZPT IAA (Indole Acetic Acid) and BAP (Benzyl Amino Purine) Vitro - Rahman Hairuddin; M. Mawariani (Universitas Sembilanbelas November Kolaka, 2021)
Bananas are a horticultural commodity that originates from Southeast Asia and the West Pacific, including Indonesia. Banana cultivation is carried out with the aim of increasing the economic value of the community by cultivating the Cavendish banana species. Cavendish banana (Musa acuminata L.) is one type of banana that is widely exported, and has high economic value. The constraints in the cultivation of this Cavendis banana plant are the small, high-quality tillers produced in large quantities and in a short time. Propagation of seeds with tissue culture technology is one solution in dealing with the problem of providing these seeds. This study aims to determine the effect of ZPT IAA and BAP concentrations on the growth of cavendish banana shoots in vitro. This research was conducted at the Tissue Culture Laboratory of the Faculty of Agriculture, Cokroaminoto University, Palopo, on Jalan Lamaranginang, Batu Pasi Village, Wara Utara District, Palopo City. Starting from January to May 2020. This research was arranged in a completely randomized design (CRD), which consisted of 5 treatments and 3 replications with a total of 15 experimental units. By giving treatment concentrations of P0: Control, P1 (IAA 0.5 mg L-1 and BAP 1 mg L-1), P2 (IAA 1 mg L-1 and BAP 2 mg L-1), P3 (IAA 1.5 mg L-1 and BAP 3 mg L-1), P4 (IAA 2 mg L-1 and BAP 4 mg L-1). With research parameters callus color, callus texture, root emergence time, shoot emergence time, number of shoots, and number of leaves. The results showed that at the concentration with treatment P3: IAA 1.5 mg L-1 and BAP 3 mg L-1 produced the highest number of leaves, namely 3 strands. The fastest root emergence time was 25.33 days and the highest number of shoots was 2.33. While for the time of emergence of treatment shoots P0: Control showed the best results, namely 7 DAS (days after planting). This is because a balanced amount of auxins and cytokinins can affect the growth of banana plants in vitro